Peningkatan Pengetahuan dan Kesadaran Lingkungan Pesisir bagi Siswa SMPN 2 dan SMPN 3 Wedung Guna Membentuk Generasi Muda yang Cinta Lingkungan - Cahyo Wulandari; Nur Ainun H.J. Pulungan; Alia Fajarwati; Nadya Aji Salsabilla; Abdurrahman Nur Prasetyo; Fatimah Az Zahra; Ghina Zain Sukmaningrum (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
The Education-Based Community Service Program for Sustainable Development (PKM PBPB) with the theme of increasing the awareness of the younger generation about the coastal environment is motivated by environmental issues in Wedung District, Demak Regency, Central Java. There are several environmental problems as well as potential in the area, including garbage and solid waste, mangrove ecosystems, eutrophication of water hyacinths in water bodies, and the need for fresh water for daily consumption. The community service is focused on the younger generation, specifically students from SMPN 2 Wedung and SMPN 3 Wedung. The methods used include an initial introduction to the coastal environment, initial assessment, socialization, education, field practice, and evaluation and assessment at the end of the activity. This program aims to increase understanding and awareness of the coastal environment for students. Socialization of materials and practices that have been carried out are about a) water desalination, b) rainwater harvesting technology in the form of biopore infiltration holes, c) introduction of mangrove plants, d) utilization of water hyacinth plants, e) waste sorting and application of zero waste,f) education on public health of coastal environments, and g) disaster mitigation for coastal communities. After conducting assessments at the beginning and end of the program, there was an increase in students’ knowledge by 9% at SMPN 2 Wedung and 14% at SMPN 3 Wedung. It can be concluded that the programs implemented in both schools have had an impact on students’ understanding of the coastal environment.